The Spanish Inquisition: a historical revision - Kamen, Henry (Yale University Press, 2014)
"In this completely updated edition of Henry Kamen's classic survey of the Spanish Inquisition, the author incorporates the latest research in multiple languages to offer a new-and thought-provoking-view of this fascinating period. Kamen sets the notorious Christian tribunal into the broader context of Islamic and Jewish culture in the Mediterranean, reassesses its consequences for Jewish culture, measures its impact on Spain's intellectual life, and firmly rebuts a variety of myths and exaggerations that have distorted understandings of the Inquisition. He concludes with disturbing reflections on the impact of state security organizations in our own time"--